Clinical validity of biochemical and molecular analysis in diagnosing Leigh syndrome: a study of 106 Japanese patients. Issue 5 (20th April 2017) - Ogawa, Erika; Shimura, Masaru; Fushimi, Takuya; Tajika, Makiko; Ichimoto, Keiko; Matsunaga, Ayako; Tsuruoka, Tomoko; Ishige, Mika; Fuchigami, Tatsuo; Yamazaki, Taro; Mori, Masato; Kohda, Masakazu; et al.
Abstract: Leigh syndrome (LS) is a progressive neurodegenerative disorder of infancy and early childhood. It is clinically diagnosed by typical manifestations and characteristic computed tomography (CT) or magnetic resonance imaging (MRI) studies. Unravelling mitochondrial respiratory chain (MRC) dysfunction behind LS is essential for deeper understanding of the disease, which may lead to the development of new therapies and cure. The aim of this study was to evaluate the clinical validity of various diagnostic tools in confirming MRC disorder in LS and Leigh‐like syndrome (LL). The results of enzyme assays, molecular analysis, and cellular oxygen consumption rate (OCR) measurements were examined. Of 106 patients, 41 were biochemically and genetically verified, and 34 had reduced MRC activity but no causative mutations. Seven patients with normal MRC complex activities had mutations in the MT‐ATP6 gene. Five further patients with normal activity in MRC were identified with causative mutations. Conversely, 12 out of 60 enzyme assays performed for genetically verified patients returned normal results. No biochemical or genetic background was confirmed for 19 patients. OCR was reduced in ten out of 19 patients with negative enzyme assay results. Inconsistent enzyme assay results between fibroblast and skeletal muscle biopsy samples were observed in 33% of 37 simultaneously analyzed cases. These data suggest that highest diagnostic rate is reached using a combined enzymatic and genetic approach, analyzing more than one type of biological materials where suitable. Microscale oxygraphy detected MRC impairment in 50% cases with no defect in MRC complex activities.